Investigating challenges and opportunities to achieve SDG 6: a study of Benin City, Nigeria - Ruth Ogbonmwan; Furat Al-Faraj (Academia Environmental Sciences and Sustainability)
Access to clean water and adequate sanitation improve sound health, enhance socio cultural development, and promote economic balance. This study focuses on investigating the challenges and opportunities to achieve Sustainable Development Goal (SDG) 6 by 2030: a case study in Benin City, Nigeria. Three local government areas in Benin City (Egor, Ikpoba-Okha, and Oredo) were selected for this study. The survey involved the use of 150 structured questionnaires administered to the people from the local government areas (LGAs). A total of 127 responses were received and processed for analysis. The data were analyzed using Microsoft Excel and Statistical Package for Social Sciences (SPSS version 27.0) software application. Although the Federal Government has put in measures such as the National Action Plan (NAP) to ensure that the objectives of SDG 6.1 and 6.2 are achieved, the findings of the study however have shown that there are still problems of accessibility, acceptability, availability, affordability, and quality. Seventy-eight percent of the respondents indicated to spend over 2,000 naira monthly on water while 86% indicated to pay extra changes to acquire water. 48.8% residents have to cover a long distance of 3 km in order to get water. 61.4% found water not to be safe for drinking while 84.3% indicated that the quality of water and sanitation in public places are of bad quality. 63.8% indicated to have challenges to availability of water and sanitation. A large percent of the residents indicated to have felt discriminated regarding water and sanitation because of their socio level. However, the study found lack of water and sanitation to be gender neutral, as both men and women are affected.